Lack of evidence of paratuberculosis in wild canids from Southwestern Europe (European Journal of Wildlife Research, 2012)
Abstract Wild carnivores are at the top of the trophic chain. They are predators and carrion consumers, and thus, prone to come in contact with disease agents contaminating the environment or infecting live or dead animals. We hypothesized that wild canids could be used as sentinels for the detection of regions with higher Mycobacterium avium paratuberculosis (MAP) prevalence in wild and domestic animals. To test this hypothesis, we set up an ELISA to test 262 wolf (Canis lupus) and fox (Vulpes vulpes) sera for MAP-specific antibodies and processed a subset of samples for culture (n?=?61), MAP-specific PCR (15) and histopathology (14). In wolves, the optical density (OD) values in the ELISA were continuously distributed. Ten fox sera (4%) had OD readings of over twice the mean, suggesting contact with mycobacteria. However, all samples tested by PCR were negative for both IS900 and ISMAP02 sequences, and samples cultured for MAP yielded no growth. No visible paratuberculosis or tuberculosis-compatible lesions were recorded. On histopathological examination, no lesions compatible with mycobacterial diseases were observed. These results suggest that wild canids show little or no evidence of paratuberculosis and are unlikely to be useful sentinels for the detection of MAP in Southwestern Europe. phone: +34-926-295450 (Gortazar, Christian) Christian.Gortazar@uclm.es (Gortazar, Christian) Instituto de Investigacion en Recursos Cinegeticos IREC (CSIC?UCLM?JCCM) - Ronda de Toledo s.n. - 13071 - Ciudad Real - SPAIN (Sobrino, Raquel) Department of Animal Production, Epidemiology & Ecology, University of Turin - 10095 - Grugliasco - ITALY (Sobrino, Raquel) Animal Health Department, NEIKER-Tecnalia - 48160 - Derio Bizkaia - SPAIN (Aurtenetxe, O.) Instituto de Investigacion en Recursos Cinegeticos IREC (CSIC?UCLM?JCCM) - Ronda de Toledo s.n. - 13071 - Ciudad Real - SPAIN (Carta, Tania) Instituto de Investigacion en Recursos Cinegeticos IREC (CSIC?UCLM?JCCM) - Ronda de Toledo s.n. - 13071 - Ciudad Real - SPAIN (Mamian, L.) Animal Health Department, NEIKER-Tecnalia - 48160 - Derio Bizkaia - SPAIN (Gerrikagoitia, X.) SERIDA, Centro de Biotecnologia Animal - 33394 - Deva-Gijon (Asturias) - SPAIN (Balseiro, A.) Instituto de Investigacion en Recursos Cinegeticos IREC (CSIC?UCLM?JCCM) - Ronda de Toledo s.n. - 13071 - Ciudad Real - SPAIN (Oleaga, A.) SERIDA, Centro de Biotecnologia Animal - 33394 - Deva-Gijon (Asturias) - SPAIN (Oleaga, A.) Animal Health Department, NEIKER-Tecnalia - 48160 - Derio Bizkaia - SPAIN (Sevilla, I. A.) Animal Health Department, NEIKER-Tecnalia - 48160 - Derio Bizkaia - SPAIN (Barral, M.) Animal Health Department, NEIKER-Tecnalia - 48160 - Derio Bizkaia - SPAIN (Garrido, J. M.) Instituto de Investigacion en Recursos Cinegeticos IREC (CSIC?UCLM?JCCM) - Ronda de Toledo s.n. - 13071 - Ciudad Real - SPAIN (Gortazar, Christian) ITALY SPAIN Registration: 2010-12-20 Received: 2010-08-23 Revised: 2010-12-16 Accepted: 2010-12-19 ePublished: 2011-01-07